the solution is (-3, -2)
Please, separate your equations with a (;) or a (.). Better yet, write only one equation per line:
Substitute 2x + 4 for y in the second equation:
3x - 6(2x + 4) = 3, or
3x - 12x - 24 = 3
Combining like terms, we get -9x = 27, and so x = -27/9, or x = -3.
Since we know that y=2x+4, we replace x in this equation with -3 and calculate y:
y = 2(-3) + 4 = -2
Then the solution is (-3, -2).
y=2x+4> equation 1
3x−6y=3> equation 2
I substitute the value of y in equation 1 for the value of y in equation 2
I substitute the value of x in equation 1 to get the value of y
y=2x+4> y=2*(-3)+4> y=-6+4
the answer is
the solution is the point (-3,-2)